Los calendarios propios de los regímenes totalitarios en el período de entreguerras. La doble datación en la documentación oficial del “bando nacional” durante la guerra civil española (1936-1939) - Francisco Olmos, José María de (Revista General de Información y Documentación, 2009)
This article deals with the problem of “alternative datings” in Europe in the first half of the 20th century, particularly in the period between wars, where totalitarian or authoritarian regimes tried to distinguish themselves through an specific dating. So we’ll see the new datings arised from politic revolutions as the soviet in Russia and the fascist in Italy and later we’ll focus in the double dating of the official documents of the “bando nacional” (national camp) during the Civil War (Año Triunfal) and after its ending (Año de la Victoria) throughout the regulations approved in the BOE and its expression in the official documentation, as could have happened with the currency, coins and notes.